An investigation of the mechanical behavior of a microswitch beam under thermal and electrostatic loading including cryogenic effect - Faris, Waleed Fekry; Mohammed , H.M.; Ng, Kok Heng (2010)
Three dimensional multiphysics finite element analysis (FEA) was performed to investigate the static and dynamic responses of a micro-switch in harsh temperature environment. The temperature range for the analysis was from -60°C to 100°C. The investigated microswitch consists of a clamped-clamped beam actuated by a bottom electrode coated with dielectric film. Coupled field simulations between the thermal, structural and electrostatic fields were performed by using the multifield solver in ANSYS. The static responses of the beam under the temperature effects were obtained from this analysis. The analysis shows that the natural frequencies were decreased with the increasing of temperature and increasing in the cryogenic range. This study will provide the designers with a tool to optimize the geometry and performance of the microswitches operated under harsh temperature environment.